Relationship between Cerebral Vein Thrombosis and Non-Anticardiolipin Antiphospholipid Antibodies - M Saadatnia; M Etemadifar; S Haghighi; V Shaigannejad; M Tajmir riahi (Journal of Research in Medical Sciences, 2004)
Background: Anticardiolipin antibody(aCL)has been recognized as a marker for increased risk of Cerebral Vein Thrombosis (CVT). However, there are only rare reports on CVT associated with other antibodies against different phospholipids such as phosphatidyl inositol, phosphatidyl serine, phosphatidic acid and beta 2 glycoprotein I. In this study, we studied the presence of these antiphospholipid antibodies (aPL), demographic and clinical characteristics in 30 patients with CVT. Methods: After diagnosis of CVT in 30 patients with MRI, we measured the titer of aCL and aPL (IgM and IgG) in all cases. The titers of IgG and IgM type of aPL and aCL were estimated in the sera. Results: Anticardiolipin antibody was solely detected in 20% (n=6) and aCL and other aPL in 23.3% ( n=7) of patients, indicating one patient positive for other aPL but not for aCL (non-aCL). Although the aPL positive group did not differ from the aPL-negative group from the stand point of clinical and demographic characteristics, yet seizure, infarct, superficial veins and sinus involvement and the use of OCP were seen more frequently in aPL-positive group Conclusion: Our findings suggest that in addition to aCL, other antiphospholipid antibodies may be an associated condition that plays a role in the pathogenesis of CVT. The presence of aPL in CVT patients is probably associated with more superficial sinus or veins involvement and as a result death rate was lower in aPL- positive group. Further investigations are necessary to establish this hypothesis. Keywords: Cerebral Vein Thrombosis, antiphospholipid antibody, anticardiolipin